(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Describe changes in knowledge and practice of preventing complications among patients with high blood pressure. Research method: One-group intervention study, describing results before and after educational intervention. Use the same set of pre-designed questions to evaluate before intervention (T1), immediately after intervention (T2), and before discharge from the hospital (T3). Results: There was a change in knowledge and practice before and after intervention: The rate of patients with knowledge about complications that can be caused by high blood pressure before intervention was low, < 40%, and after T3 intervention all achieved over 60%. The rate of knowledge assessment on how to handle paroxysmal hypertension ranges from 15% (T1) to 82% (T3). After the intervention, patients’ practice also changed significantly: from 4% (T1) to 63% (T3) of patients measured blood pressure daily. The rate of risk factors such as using extra salt and fish sauce in processing, eating salty foods, using animal fat, smoking cigarettes, waterpipe tobacco, and drinking alcohol after intervention all decreased to less than 10%. The rate of correct answers about measures taken to prevent stroke after intervention is over 60%. The rate of not knowing decreased from 58% (T1) to 5% (T3). Conclusion: After health education intervention, the proportion of patients with knowledge about preventing complications of hypertension receiving inpatient treatment at Quan Ninh Traditional Medicine Hospital increased. Hospitals need to regularly maintain educational intervention programs for patients to increase treatment effectiveness.